(untitled) (HORIZON: Indonesian Journal of Multidisciplinary, 2026)
This study aims to analyse the influence of workload and work motivation on employee loyalty, with performance-related pay acting as a mediating variable, at the Regional Development Planning Agency (Bappeda) of Konawe Kepulauan Regency. The study employs a quantitative approach using a survey method. The study population comprises all 35 employees of Bappeda Konawe Kepulauan Regency, all of whom served as respondents. Data were collected via a five-point Likert scale questionnaire and analysed using Partial Least Squares-based Structural Equation Modelling (SEM-PLS). Data analysis included measurement model testing (convergent validity, discriminant validity, and reliability) as well as structural model testing to assess direct and indirect relationships between variables. The results of the analysis indicate that workload and work motivation have a positive and significant effect on performance-related allowances. Workload, work motivation, and performance-related allowances also have a positive effect on employee loyalty. Furthermore, performance-related allowances were found to mediate the influence of workload and work motivation on employee loyalty. These findings suggest that the management of workload and the enhancement of work motivation, supported by a fair and proportionate performance-related pay system, play a crucial role in strengthening employee loyalty.